Franklin County: Agriculture as a “Sleeping Giant” - Swain, Tanya (Maine Policy Review, 2011)
Franklin County, Maine was once a major farming area. This case study describes efforts underway to revive and grow agriculture in this rural area in the state’s western mountains
Keywords: Maine; food production; agriculture